Respuesta :

Answer:

[tex]f(x)=-(x+8)(x-2)[/tex]

Step-by-step explanation:

Start by factoring out a -1...

[tex]f(x)=-(x^2+6x-16)[/tex]

Now, we have to find two integers that multiply to get -16 and have a sum of 6:

(-2)*8=-16

-2+8=8-2=6

Using this, we can split 6x into -2x and 8x...

[tex]f(x)=-(x^2-2x+8x+16)[/tex]

Factor  the first and second half separately...

[tex]f(x)=-[(x^2-2x)+(8x-16)]\\f(x)=-[x(x-2)+8(x-2)]\\[/tex]

Since both x and 8 are being multiplied by x-2, we can combine them to get...

[tex]f(x)=-(x+8)(x-2)[/tex]